High CO2 separation performance on a metal–organic framework composed of nano-cages lined with an ultra-high density of dual-side open metal sites. Issue 1 (19th November 2021) - Li, Liangjun; He, Jiangxiu; Xu, Wenli; Zhang, Kuitong; Xing, Tao; Li, Zhi; Zhen, Dewen; Xiong, Bo; Ge, Zhixing; Zhang, Xi; Wang, Shanyu; Zhang, Fuzhao; et al.
Abstract : High CO2 separation performance on a microporous MOF incorporting nano-cages and an ultra-high density of dual-side open metal sites is reported. Abstract : Developing efficient adsorbents for CO2 separation is the crucial step of CO2 sequestration. which has found many applications, including in carbon capture from flue gas and natural gas purification. Although many adsorbents have been reported in the past few decades, developing efficient adsorbents with high separation selectivity and excellent capacity is technically challenging due to the trade-off effect between the adsorption capacity and selectivity. This work reports the CO2 separation performance of a microporous MOF, which comprises nano-cages and an ultra-high density of dual-side open metal sites. The adsorption results reveal a prominent CO2 uptake and outstanding separation selectivity for CO2 /N2 and CO2 /CH4 . Furthermore, this MOF also exhibits the preferable adsorption of C2–C3 light hydrocarbons over CH4 . Simulation studies reveal that the dual-side open metal sites are the preferable adsorption sites for CO2, C2 H4, and C3 H6 . Therefore, the outstanding separation performance can be attributed to the combined effects of nano-cages and the high density of open metal sites.